Polhemus EM tracked Micro Sensor for CT‐guided interventions. Issue 1 (4th December 2018) - Franz, Alfred M.; Seitel, Alexander; Cheray, Dominique; Maier‐Hein, Lena
Abstract : Purpose: Electromagnetic (EM) tracking is a key technology in image‐guided therapy. A new EM Micro Sensor was presented by Polhemus Inc.; it is the first to enable localization of medical instruments through their trackers. Different field generators (FGs) are available by Polhemus, one being almost as small as a sugar cube. As accuracy and robustness of tracking are known challenges to using EM trackers in clinical environments, the goal of this study was a standardized assessment of the Micro Sensor in both a laboratory (lab) and a computed tomography (CT) environment. Methods: The Micro Sensor was assessed by means of Hummel et al.'s standardized protocol; it was assessed in conjunction with a Polhemus Liberty tracker and three FGs — with edge lengths of 1 (TX1), 2 (TX2), and 4 (TX4) inches. Precision as well as positional and rotational accuracy were determined in a lab and a CT suite. Distortions by four different metallic cylinders and tracking of two typical medical instruments — a hypodermic needle and a flexible endoscope — were also tested. Results: A jitter of 0.02 mm or less was found for all FGs in the different environments, except for the TX2 FG for which no valid data could be obtained in the CT. Errors of 5 cm distance measurements were 0.6 mm or less for all FGs in the lab. While the distance errors of the TX1 FG were only slightly increased up to 1.6 mm in the CT, those of the TX4 FG were found to be up to around 10% of the measured distance (5.4 mm on average). The mean orientation error was found to be 0.9 ° /0.5 ° /0.1 ° for the TX4/TX2/TX1 FG in the lab. In the CT environment, rotation errors were in the same range: less than 1.2 ° /0.1 ° for the TX4/TX1 FG. Deviation under the presence of metallic cylinders stayed below 1 mm in most cases. Precision and orientational accuracy do not seem to be affected by instrument tracking and stayed in the same range as for the other measurements whereas distance errors were slightly increased up to 1.7 mm. Conclusion: This study shows that accurate tracking of medical instruments is possible with the new Micro Sensor; it demonstrated a jitter of 0.01 mm or less, position errors below 2 mm, and rotation errors of less than 0.3 ° . As with other EM trackers, errors increase when large tracking volumes with ranges of up to 50 cm are required in clinical environments. For smaller tracking volumes with ranges of up to 15 cm, a high accuracy and robustness was found. This is interesting especially for the TX1 FG which can easily be placed in close vicinity to the region of interest.